(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This article analyses the terrible conditions of Afghan refugees through the characters in Khaled Hosseini’s novels The Kite Runner, A Thousand Splendid Suns, and Andthe Mountain Echoed. Hosseini is a well-known Afghan-American author. He has written three novels and one collection of short stories. All the three books investigate the significance of Afghan culture. Those books, in particular, reflect the situation and suffering of Afghans, particularly Afghan women. Faith, heritage, identity crises, cultural traditions, and way of life are all important components of the Afghan people. Human misery is the most prominent feature of Afghan society. Women who become refugees face numerous challenges, including a difficult journey, the loss of family members and property, and different cultures in the country of immigration. The majority of Afghans in the United States are unable to return home because to persistent political upheaval in their nation, which has the world’s largest refugee population. Psychological distress can manifest itself in a variety of ways in different persons. Because of the circumstances surrounding their departure from their home country, some refugees have a unique aversion to persons in positions of power.